Molecular and serological characterization of occult hepatitis B virus infection among patients with hemophilia. Issue 8 (9th April 2019) - Javanmard, Davod; Namaei, Mohammad Hasan; Farahmand, Mohammad; Ziaee, Arash; Amini, Elham; Ziaee, Masood
Abstract: Background: The occult hepatitis B virus infection (OBI) is a health concern among high‐risk groups and immunosuppressed individuals. There is still a paucity of data regarding the occult hepatitis B virus infection among hemophilic patients. With this in mind, we aimed to evaluate the molecular prevalence of OBI among clients with hemophilia. Methods: Totally, 87 hemophilic patients were selected to be studied. To detect OBI, nested polymerase chain reaction test was used to amplify HBV‐S, X, and Core regions. Viral load was determined using an in‐house real‐time PCR assay. Finally, sequence of S gene was used for genotyping and analysis of mutations. Results: The mean age of patients was 28.4 ± 5.3 years old, with 90.7% of whom were men. HBV‐DNA was detected in eight subjects (9.3%). The rate of OBI was much higher in anti‐HBs seronegative subjects than that in other patients ( P  = 0.019). All OBI cases had HBV genotype D, subgenotype D1. In addition, five out of eight cases (62.5%) showed detectable viral loads (a mean viral load of 4.5 × 10 2 copies/mL). sR73H, sI110L, sP120A, sP127T, sQ129H, sG130R, and sC137S were shown to be the most determinant escape mutation and OBI‐relevant mutants. Conclusion: The rate of OBI among the studied population of hemophilia seems to be remarkable. Therefore, screening for OBI must be a routine practice in patients with hemophilia and also patients undergoing immunosuppressive treatments. Amino acid substitutions were observed in the major hydrophilic region. However further investigations are needed for analysis of exact function.